Follow-up Study on the Outcomes of Recovered Pregnant Women with a History of COVID-19 in the First and Second Trimesters: A Case Series from China. Issue 1 (11th January 2021) - Zhao, Yin; Huang, Bangxing; Ma, Hui; Shang, You; Nie, Xiu; Zou, Li
Abstract: Objective: To determine the pregnancy and neonatal outcomes of women who recovered from coronavirus disease 2019 (COVID-19) that developed in early pregnancy. Methods: This case series analyzed five pregnant women (26–33 years) whom recovered from COVID-19 which were developed in early pregnancy (6–27 weeks) and admitted at the Wuhan Union Hospital from January 15, 2020 to April 30, 2020. The clinical manifestation, laboratory examinations, treatment, pregnancy outcomes, maternal and neonatal severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) throat swab reverse transcription polymerase chain reaction test results, and SARS-CoV-2 antibody test results in neonates were reviewed. The placental pathology, placental angiotensin-converting enzyme 2 expression were studied by hematoxylin-eosin and immunohistochemistry staining, SARS-CoV-2 presence was examined by QT-PCR. We also followed up the infants at 3–6 months. Results: Three pregnant women were diagnosed with COVID-19 in early pregnancy (Cases 1–3), and two were serum immunoglobulin G positive asymptomatic cases (Cases 4 and 5). Cases 1–3 showed complete recovery after severe COVID-19. Case 3 was infected at 6 weeks of gestation during the first trimester and had induced medical abortion at 12 weeks of gestation. All neonates had no pneumonia, SARS-CoV-2 mRNA reverse transcription polymerase chain reaction and serum immunoglobulin M were negative, and immunoglobulin G were positive. All placental samples were negative for SARS-CoV-2 in the nucleic acid test. Placental pathology showed chronic ischemia changes. ACE-2 expressed in both placenta and decidua. The follow-up showed that the infants were healthy and asymptomatic at 3–6 months. Conclusion: No adverse outcomes was observed in our case series. However, systemic inflammatory responses to SARS-CoV-2 infection may cause placental injury. At the time of delivery after recovery from COVID-19, no SARS-CoV-2 positive results was found in the placenta in this case series.